COMMUNITY EMPOWERMENT PROGRAM TO INCREASE COMMUNITY INCOME IN SITIMULYO VILLAGE, PIYUNGAN DISTRICT, YOGYAKARTA - Cristina, Heppi Marta (Jurnal Penelitian Humaniora, 2020)
The community empowerment program is a program provided to the community by conducting training to improve human resources and community income through local governments. The purpose of this study was to analyze the community empowerment program that will be implemented to increase community income in the Sitimulyo Village, Piyungan District, Bantul, Yogyakarta. Qualitative research method was used. The number of samples in the study were 30 respondents, data collection techniques used interviews supported by observation as well as secondary data and primary data. The results showed that the community empowerment program with the OVOP approach with training related to activities to increase skills development and entrepreneurship had been carried out by village officials through village community empowerment activities. That the empowerment program through the OVOP approach or One Vilage One Product is a training carried out by the local government, especially village officials with activities to increase community income through skills training and entrepreneurship by participating in the community in a good rated training program that will be given to the community successfully because of the enthusiasm of the invited community in following the training program. Village officials always try to provide any kind of assistance in terms of tools, materials and services for the success of the community empowerment program. This training program will increase community knowledge and skills in making a product by utilizing a variety of local food and so on until it can be produced which can later become an entrepreneur.Community empowerment with the OVOP approach is an empowerment program directed at (1) enabling, namely the creation of a climate capable of encouraging the development of community potential, (2) empowering, namely the potential possessed by the community is further strengthened and (3) protecting the potential of the weak community in all respects balanced protection is needed so that the competition formed runs healthily in an effort to make the community have the ability to run a business so as to increase people's income.